2020
DOI: 10.3390/ijms21051899
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Low Activity of Transport System A for Neutral Amino Acids in Human Bone Marrow Mesenchymal Stem Cells

Abstract: In cultured human fibroblasts, SNAT transporters (System A) account for the accumulation of non-essential neutral amino acids, are adaptively up-regulated upon amino acid deprivation and play a major role in cell volume recovery upon hypertonic stress. No information is instead available on the expression and activity of SNAT transporters in human bone marrow mesenchymal stromal cells (MSC), although they are increasingly investigated for their staminal and immunomodulatory properties and used for several ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The repertoire of amino acid transporters in human MSCs has been only recently evaluated in stromal cells from healthy donors. 40 Comparing the expression of several transporters for Asn and Gln in HD- and ALL-MSCs, we found that SLC38A5 , the gene that encodes for the transporter SNAT5, is significantly more expressed in mesenchymal cells from ALL patients. Consistently, Asn efflux is significantly faster in ALL-MSCs than in HD-MSCs, suggesting that SNAT5 is the carrier exploited for Asn secretion by stromal cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The repertoire of amino acid transporters in human MSCs has been only recently evaluated in stromal cells from healthy donors. 40 Comparing the expression of several transporters for Asn and Gln in HD- and ALL-MSCs, we found that SLC38A5 , the gene that encodes for the transporter SNAT5, is significantly more expressed in mesenchymal cells from ALL patients. Consistently, Asn efflux is significantly faster in ALL-MSCs than in HD-MSCs, suggesting that SNAT5 is the carrier exploited for Asn secretion by stromal cells.…”
Section: Discussionmentioning
confidence: 88%
“…However, the pro-survival intercellular amino acid flux implies the activity of amino acid transporters. The repertoire of amino acid transporters in human MSCs has been only recently evaluated in stromal cells from healthy donors 40 . Comparing the expression of several transporters for Asn and Gln in HD-and ALL-MSCs, we found that SLC38A5, the gene that encodes for the transporter SNAT5, is significantly more expressed in mesenchymal cells from ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Preincubation was done with 500 μL of prewarmed HBSS at 37 °C for 10 min before adding substrates (250 μL in HBSS) for the uptake experiments. The functionality of SNATs in MCF-7 cells was studied with a known SNAT substrate; the cells were incubated either with [ 3 H]- l -proline [1 μM (PerkinElmer, Waltham, MA, USA) in uptake buffer HBSS, 250 μL] at 37 °C for 1–60 min or with the uptake buffer (250 μL) consisting of 1–600 μM l -proline (containing 2 μCi [ 3 H]- l -proline) at 37 °C for 60 min . After incubation, the uptake was stopped by adding 500 μL of ice-cold HBSS, and the cells were washed two times with ice-cold HBSS (2 × 500 μL).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The functionality of SNATs in MCF-7 cells was studied with a known SNAT substrate; the cells were incubated either with [ 3 H]- l -proline [1 μM (PerkinElmer, Waltham, MA, USA) in uptake buffer HBSS, 250 μL] at 37 °C for 1–60 min or with the uptake buffer (250 μL) consisting of 1–600 μM l -proline (containing 2 μCi [ 3 H]- l -proline) at 37 °C for 60 min. 38 After incubation, the uptake was stopped by adding 500 μL of ice-cold HBSS, and the cells were washed two times with ice-cold HBSS (2 × 500 μL). The cells were then lysed with 500 μL of 0.1 M NaOH (60 min), and the lysate was mixed with 3.5 mL of Emulsifier safe cocktail (Ultima Gold, PerkinElmer, Waltham, MA, USA).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Through glutamate, Gln sustains the synthesis of GSH (also fueled by cysteine/Glu exchange, see above) and several non–essential amino acids (NEAAs). Moreover, Gln is a precursor for nucleotides and glucosamine and behaves as a compatible osmolyte to maintain cell volume under hypertonic conditions ( Chiu et al, 2020a ). In addition, through its capability to interact with several active and exchange transporters, it is accumulated at high levels into the cell and can fuel by exchange the uptake of many NEAA and essential amino acids (EAAs).…”
Section: Glutaminementioning
confidence: 99%